2013
DOI: 10.1371/journal.pone.0078298
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Food and Nutrient-Based Standards on Primary School Children’s Lunch and Total Dietary Intake: A Natural Experimental Evaluation of Government Policy in England

Abstract: In 2005, the nutritional content of children’s school lunches in England was widely criticised, leading to a major policy change in 2006. Food and nutrient-based standards were reintroduced requiring primary schools to comply by September 2008. We aimed to determine the effect of the policy on the nutritional content at lunchtime and in children’s total diet. We undertook a natural experimental evaluation, analysing data from cross-sectional surveys in 12 primary schools in North East England, pre and post pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 19 publications
(15 reference statements)
5
36
1
4
Order By: Relevance
“…However, a previous study investigating differences in intake by lunch type in younger children aged 4-6 years reported similar findings to this research (37) .…”
Section: Discussionsupporting
confidence: 89%
“…However, a previous study investigating differences in intake by lunch type in younger children aged 4-6 years reported similar findings to this research (37) .…”
Section: Discussionsupporting
confidence: 89%
“…These policies ranged from removal of sugar-sweetened beverages (SSBs) and junk food [2830]; change in canteen policies (increasing the availability of lower-fat foods in cafeteria’s à la carte areas and implementing school-wide, student-based promotions of these lower-fat foods) [31]; school self-assessment; nutrition education; nutrition policy (meet nutritional standards based on Dietary Guidelines for Americans); social marketing; and parent outreach [14]; fruit truck shops [32]; nutrition education and gardening program [33]; brisk walking lessons [22]; integration of health promotion in curriculum [27]; teacher trainings and development of activities related to food habits and/or physical activity [23]; fitness guidance, fitness and school nutrition, school-based nutrition, school and home nutrition and home-based nutrition [26]; modified school lunches, enhanced nutrition education and increased opportunities for physical activities [34]; comprehensive school health education, physical education and physical activity, school nutrition and food services, health promotion and wellness, school counselling, physical and behavioral health services, school climate, physical environment, youth, parent, family and community involvement [35]. Six out of seven studies assessing policy effectiveness in reduction of sugar intake reported desirable changes and reduction in sugar or SSBs consumption [21, 26, 28, 29, 35, 36]. These effective policies included elimination of SSB and other junk food in schools’ food policy, having a school food and nutrition policy in place, school district SSB policies, school nutrition and food services, nutrition-based standards and fitness guidance, fitness and school nutrition, school-based nutrition, school and home nutrition and home-based nutrition.…”
Section: Resultsmentioning
confidence: 99%
“…Out of these effective interventions, teacher training and development of activities related to food habits and/or physical activity and fruit truck shops were observed to be reported from studies with moderate and strong methodological quality. Regarding fat reduction and salty snacks, school dietary policies were reported to reduce their prevalence [26, 30, 36] (Table 4). All the three studies were judged to have weak methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…These findings point to the potential value of strengthening food policies to prevent obesity. Possible priorities for Russia might be expanding school food policies, improving the labeling provisions on food packaging, restricting marketing, and influencing the price of foods high in fats, salt, and free sugars [18, 19]. Effective interventions on associated risk factors such as BP and cholesterol may be available when diagnosed, and they might help to lessen the cardiovascular effects of obesity [20].…”
Section: Discussionmentioning
confidence: 99%